Evolution and Distribution of C(7)-Cyclitol Synthases in Prokaryotes and Eukaryotes - Osborn, Andrew R. (ACS Chem Biol, 2017)
2-epi-5-epi-Valiolone synthase (EEVS), a C(7)-sugar phosphate cyclase (SPC) homologous to 3-dehydroquinate synthase (DHQS), was discovered during studies of the biosynthesis of the C(7)N-aminocyclitol family of natural products. EEVS was originally thought to be present only in certain actinomycetes, but analyses of genome sequences showed that it is broadly distributed in both prokaryotes and eukaryotes, including vertebrates. Another SPC, desmethyl-4-deoxygadusol synthase (DDGS), was later discovered as involved in the biosynthesis of mycosporine-like amino acid sunscreen compounds. Current database annotations are quite unreliable, with many EEVSs reported as DHQS, and most DDGSs reported as EEVS, DHQS, or simply hypothetical proteins. Here, we identify sequence features useful for distinguishing these enzymes, report a crystal structure of a representative DDGS showing the high similarity of the EEVS and DDGS enzymes, identify notable active site differences, and demonstrate the importance of two of these active site residues for catalysis by point mutations. Further, we functionally characterized two representatives of a distinct clade equidistant from known EEVS and known DDGS groups, and show them to be authentic EEVSs. Moreover, we document and discuss the distribution of genes that encode EEVS and DDGS in various prokaryotes and eukaryotes, including pathogenic bacteria, plant symbionts, nitrogen-fixing bacteria, myxobacteria, cyanobacteria, fungi, stramenopiles, and animals, suggesting their broad potential biological roles in nature.